Os estereótipos e o efeito do contato virtual no preconceito contra negros e nordestinos - Batista, José Roniere Morais (2014)
The main objective of this thesis was to investigate the role of the contact maintained via internet with Blacks and Northeasterners in the relationship between prejudice and discrimination against these groups. To achieve the proposed objective, five studies were carried out. In the first three, the instruments that would later be used were developed, and the similarities and differences between regional and racial bias were established. In the last two studies, the aim was to investigate the role of types of contact (maintained on the Internet, in-person, and extended) in the perception of bias against groups of Blacks and Northeasterners, as well as their roles in mediating the relationship between prejudice and discrimination. To carry out study 1, a list of adjectives was used where participants chose the most representative features of the groups of Blacks and Northeasterners. The results of study 1 indicated a strong similarity in assigning adjectives to the group of Northeasterners and Blacks. This process of stereotyping was similar to that found in surveys conducted ten years earlier with groups of Blacks, which demonstrates a constancy of the content of these stereotypes. Study 2 contained the list of adjectives used in Study 1, as well as measures of prejudice and identification with the group of Blacks and Northeasterners. The main result was the evidence of the existence of a process of essentialization in the categorization of Northeasterners, similar to what happens with the group of Blacks. In this sense, the Northeasterners were not evaluated in terms of the characteristics of their region, but by stereotypes referencing natural and biological characteristics, thus approaching the existing explanations for racial prejudice. To conduct study 3, a scenario was developed where an alleged unfair selection occurred during the hiring process for a position as salesman in a store. The context of injustice varied over two conditions. In the first, a black person competing with a white person for the position, the latter was hired, even though both had the same qualifications. In the second condition, the story was the same, with a northeasterner competing with a southern candidate for the position as salesman, and the latter was hired. It was up to the participants to judge the selection as fair or unfair, and then explain their answers. The results showed a similarity in the discursive repertoires for both conditions: the Black individual and the Northeasterner, which corroborates the results of studies 1 and 2. To carry out studies 4 and 5, measures of contact were used, which were categorized in three ways: contact maintained via Internet (number of friends that participants had exclusively in the virtual environment); personal contact (number of friends that participants had in their everyday relationships); and extended contact (number of friends and relatives that respondents possessed and which were related to the group of Blacks and Northeasterners). The results of study 4 presented contact maintained on the internet with Blacks and Northeasterners as a better predictor of perceived discrimination committed against these groups. The result of study 5 indicated that the internet contact maintained with Blacks and Northeasterners mediated the relationship between prejudice and discrimination, such that the more contact maintained with Blacks and Northeasterners on the internet, the lower were the rates of discrimination against these groups. Taken together, the results indicate that contact via internet with Blacks and Northeasterners may have a positive effect in building a more positive image of these groups.